The Effect of Using Quizizz Application on Senior High School Students’ Reading Comprehension Achievement in Jatiroto - Fachrudin Ken Ariyanto (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
English has become one of the most widely used languages for communication by the international community as stated by Putra, (2020). To support this purpose, reading is one of the important basic skills that must be mastered to understand the meaning of information. Gilakjani & Sabouri (2016) stated that finding the right message in a text that the author meant for the reader to understand is the main goal of reading. Because of this, reading is a crucial skill that students have to master alongside other skills such as listening, speaking, and writing. However, reading becomes a problem for most students because the learning media provided by the teacher in teaching reading is sometimes too monotonous as stated by Kamalova & Koletvinova (2016). Students' reading interest is also a point that must be considered in order to increase their motivation to read. Salikin et al., (2017) in their research found that most students lack of interest in reading, especially when it comes to English as their second language. This is because they only consider it as a subject, not as an international language requirement. Nowadays, there are many choices of applications that can be used by teachers to optimize classroom learning. For example, the teacher can apply Quizizz as their learning media. Quizizz already implements the use of audio-visual media in their application. As stated by Suyitno et al., (2020) this media can be used to attract students' interest during learning by using interesting images and sounds so that students can enjoy enjoying the topic being discussed. This research was aimed to find out whether there is any difference in reading comprehension between the students who are taught by Quizizz and those who are not. This research was conducted at one of the senior high schools in Jatiroto, East Java by implementing quasi-experimental design and using post-test only design as the tool to collect the data about the students’ reading comprehension xiv achievement score. The researcher used participants from grade ten because they had never used the help of the Quizizz application in learning. The participants in this research were divided into control and experimental groups. This research was conducted from September 25th to October 23rd, 2024. The result of the data analysis carried out by using the researcher using an independent sample T-test with the help of the SPSS program to determine whether or not the mean of the experimental group is higher than the control group. The mean score of the experimental group was 75.33 with a standard deviation of 9.643. Meanwhile, the mean score of the control group was 68.50 with a standard deviation of 9.299. The results of the post-test score analysis show that the experimental group had a higher mean score than the control group. Based on the results of the sample t-test analysis by using SPSS, it was found that the degree of freedom (df) of the post-test was 58. In these outputs, the part that must be considered is sig. (2 tailed) as the main reference whether there is a significant difference or not between control and experimental group. The result of the sig. (2 tailed) value is 0.007 (smaller than 0.05). From these results it can be concluded that there is a significant difference between the control group and the experimental group. In other words, there is a significant difference from the use of Quizizz in the achievement of students' reading comprehension. In short, it was revealed that Quizizz has a significant effect on the reading comprehension achievement of tenth grade students at one senior high school in Jatiroto. The limitation of this research is the total number of participants which 60 students and targeted high school which only one were small numbers in comparison in total amount of students and schools that has implemented Quizizz in Indonesia, therefore for future researchers can use other skills besides reading, writing skills for example. Related to the texts used, future researchers can also use other texts besides descriptive texts because other types of texts can also be explored. It is highly recommended for future researchers to prepare more time to ensure that all students are able to use and can participate in the research properly.Another replication of the research at other learning levels is also highly recommended.
Reuploud Repository hasyim Juni 2026
Keywords: Quizizz Application; Reading Comprehension Achievement